Anthocyanin recovery from grape by-products by combining ohmic heating with food-grade solvents: phenolic composition, antioxidant, and antimicrobial properties - Coelho, Marta (2021)
Usually, wine-making by-products are discarded, presenting a significant environmental impact. However, they can be used as a source of bioactive compounds. Moreover, consumers’ increasing demand for naturally nutritious and healthy products requires new formulations and food product improvement, together with sustainable, environmentally friendly extraction methods. Thus, this work aimed to compare ohmic heating (OH) with conventional methodology (CONV), using food-grade solvents, mainly water, compared to standard methanol extraction of anthocyanins. No significant differences were found between the CONV and OH for total phenolic compounds, which were 2.84 ± 0.037 and 3.28 ± 0.46 mg/g DW gallic acid equivalent, respectively. The same tendency was found for antioxidant capacity, where CONV and OH presented values of 2.02 ± 0.007 g/100 g and 2.34 ± 0.066 g/100 g ascorbic acid equivalent, respectively. The major anthocyanins identified were malvidin-3-O-acetylglucoside, delphinidin-3-O-glucoside, petunidine-3-O-glucoside, cyanidin-3-O-glucoside, and peonidine-3-O-glucoside. These extracts displayed antimicrobial potential against microorganisms such as Yersinia enterocolitica, Pseudomonas aeruginosa, Salmonella enteritidis, methicillin-sensitive Staphylococcus aureus, a methicillin-resistant Staph. aureus (MRSA), and Bacillus cereus. In conclusion, OH provides similar recovery yields with reduced treatment times, less energy consumption, and no need for organic solvents (green extraction routes). Thus, OH combined with water and citric acid allows a safe anthocyanin extraction from grape by-products, thus avoiding the use of toxic solvents such as methanol, and with high biological potential, including antimicrobial and antioxidant activity.